永磁平面齿轮实验研究 - 赵文秀; 高鹏; 李昊宇; 戴恒震; 华顺刚 (Jixie chuandong)
A new type of permanent magnetic face gear which couple through multi-row magnetic cylinders and achieve non-contact orthogonal transmission is proposed.Through several experiments of this permanent magnetic gears device,its transmission characteristics and influencing factors are studied,finding that the air gap directly affects magnetic coupling drive torque.By comparing of torque curves of different starting angle as well as the different curves of a certain single row of magnetic cylinders,the condition of better transmission characteristic is obtained.No matter device is on load or not,the research phenomena indicate that the device runs smoothly.By measuring the magnetic field and its changes in engagement region,the analysis result is further validated,and the transmission characteristics can be improved on the basis of rational distribution of the magnetic cylinders.